Subplate neurons: crucial regulators of cortical development and plasticity - Kanold, Patrick O. (Frontiers in Neuroanatomy, 2009)
The developing cerebral cortex contains a distinct class of cells, subplate neurons, which form one of the first functional cortical circuits. Subplate neurons reside in the cortical white matter, receive thalamic inputs and project into the developing cortical plate, mostly to layer 4. Subplate neurons are present at key time points during development. Removal of subplate neurons profoundly affects cortical development. Subplate removal in visual cortex prevents the maturation of thalamocortical synapse, the maturation of inhibition in layer 4, the development of orientation selective responses in individual cortical neurons, and the formation of ocular dominance columns. In addition, monocular deprivation during development reveals that ocular dominance plasticity is paradoxical in the absence of subplate neurons. Because subplate neurons projecting to layer 4 are glutamatergic, these diverse deficits following subplate removal were hypothesized to be due to lack of feed-forward thalamic driven cortical excitation. A computational model of the developing thalamocortical pathway incorporating feed-forward excitatory subplate projections replicates both normal development and plasticity of ocular dominance as well as the effects of subplate removal. Therefore, we postulate that feed-forward excitatory projections from subplate neurons into the developing cortical plate enhance correlated activity between thalamus and layer 4 and, in concert with Hebbian learning rules in layer 4, allow maturational and plastic processes in layer 4 to commence. Thus subplate neurons are a crucial regulator of cortical development and plasticity, and damage to these neurons might play a role in the pathology of many neurodevelopmental disorders.